Abstracts of papers presented at National Congress, Pretoria, April 1991 - Editorial Office (AOSIS, 1991)
Gross motor classes for severely to profoundly retarded mentally handicapped by J.A.C. Gilder. Lentegeur Hospital. Physiotherapeutic management of Guillain-Barré patients in the Johannesburg hospital by L. Hale. Physiotherapy Department, Johannesburg Hospital. Pressure sores in paraplegia: Where are we now? by R. Henn. Physiotherapy Department, Rand Mutual Hospital. Low power infra-red laser irradiation in the treatment of chronic tendinitis in athletes by L. Jankelowitz. Discipline of Sport Science, Medical School, University of Cape Town.